Book of the electroporation-based technologies and treatments - Kramar, Peter (knjige, 2023)
This book covers the latest and most to date information on electroporation, electropermeabilisation and pulsed power fields. It provides concise introduction to the topic covering basic knowledge and biomedical applications that anyone in the field needs to understand in order to be successful.
Keywords: celične membrane; elektrokemoterapija; Elektroporacija; lipidni dvosloji; tkiva; Zborniki